Daya Saing Buah Tropis Indonesia Di Pasar Asia Tenggara - Zainudin, Ahmad; Permatasari, Adinda (Politeknik Negeri Lampung, 2024)
Tropical fruit is a potential commodity, contributing 54.7% to the national horticulture GDP, included in the main component of the Pola Pangan Harapan, and a part of Southeast Asia's national horticulture development goals. Fruits with the highest export value are mangoes, mangosteens, guavas, oranges, and watermelons. This study aims to determine the export competitiveness of Indonesian tropical fruit commodities in the Southeast Asian market. The research methods used Revealed Comparative Advantages (RCA), Export Product Dynamics (EPD), Intra Industry Trade (IIT). The results showed that based on RCA analysis, the fruits with strong competitiveness were mango, mangosteen and guava, pineapple, and watermelon in Malaysia and Timor Leste. The EPD analysis results show that most Indonesian tropical fruit in Malaysia is in the Rising Star position, Timor Leste Lost Opportunity, and Singapore Retreat and Falling Star. IIT analysis shows that trade integration between Indonesia and Malaysia is in moderate indicators, and Singapore and Timor Leste is still weak.